Anatomical investigation of potential contacts between climbing fibers and cerebellar Golgi cells in the mouse - Galliano, Elisa; Baratella, Marco; Sgritta, Martina; Ruigrok, Tom J.; Haasdijk, Elize D.; Hoebeek, Freek E.; D‘Angelo, Egidio; Jaarsma, Dick; De Zeeuw, Chris I. (Frontiers in Neural Circuits, 2013)
Climbing fibers (CFs) originating in the inferior olive (IO) constitute one of the main inputs to the cerebellum. In the mammalian cerebellar cortex each of them climbs into the dendritic tree of up to 10 Purkinje cells (PCs) where they make hundreds of synaptic contacts and elicit the so-called all-or-none complex spikes controlling the output. While it has been proven that CFs contact molecular layer interneurons (MLIs) via spillover mechanisms, it remains to be elucidated to what extent CFs contact the main type of interneuron in the granular layer, i.e., the Golgi cells (GoCs). This issue is particularly relevant, because direct contacts would imply that CFs can also control computations at the input stage of the cerebellar cortical network. Here, we performed a systematic morphological investigation of labeled CFs and GoCs at the light microscopic level following their path and localization through the neuropil in both the granular and molecular layer. Whereas in the molecular layer the appositions of CFs to PCs and MLIs were prominent and numerous, those to cell-bodies and dendrites of GoCs in both the granular layer and molecular layer were virtually absent. Our results argue against the functional significance of direct synaptic contacts between CFs and interneurons at the input stage, but support those at the output stage.